Ultrasonic Characterization of Bi2(Te1-xSex)3 System - GAAFAR, Mohamed El-Sayed; SOLIMAN, Laila Ibrahim; MARZOUK, Samir Yousuf (Archives of Acoustics, 2009)
Longitudinal and shear ultrasonic wave velocities were measured in the ternary compounds B2(Te1-xSex)3 (0[ampersand]le;x[ampersand]le;1), using pulse echo technique. Measurements were carried out at 4MHz frequency and at room temperature. Elastic moduli and acoustic impedance have been calculated. The results indicate that these parameters are influenced by the increased addition of selenium from x=0 to 1.